Clinical Features and Outcome of SARS-CoV 2 Virus Infection in Patients with Autoimmune Diseases - Perveen, Shahida; Salim, Babur; Faisal, Mohammad Jamal; Samreen, Saba (Pakistan Armed Forces Medical Journal, 2022)
Objectives: To evaluate the clinical features, outcome and poor prognostic factors of COVID-19 in rheumatic disease patients. Study Design: Cross-sectional study. Place and duration of Study: Department of Rheumatology, Fauji Foundation Hospital, Rawalpindi, from Mar to Sep 2020. Methodology: The study included rheumatic disease patients with COVID-19. Patients’ age, gender, smoking status; details of rheumatic disorder; method of COVID-19 diagnosis, treatment and outcomes were recorded. Results: The study included 46 patients. Overall mortality rate was 23.8%. The most common symptoms were fever (35, 83.3%), cough (26, 61.9%) and myalgia (23, 54.8%). Dyspnea was associated with mortality (p=0.013), ICU admission (p<0.001), ventilation (p=0.02) and hospitalization (p<0.001). NSAIDs increased the risk of ventilatory support (p= 0.02). Long term steroids predicted mortality (p=0.02), hospitalization (p=0.014) and intensive care admission (p=0.004). Steroid and Hydroxy-chloroquine treatment for COVID-19 was associated with intensive care admission (p= 0.001 and 0.006, respectively) and ventilation (p=0 .007 and 0.03, respectively). Mycophenolate Mofetil was related to intensive care admission, ventilation and hospitalization (p=0.03, 0.03 and 0.02, respectively), whereas Cyclophosphamide was related to hospitalization (p= 0.03). Systemic lupus erythematosus was associated with all poor outcomes except ventilation (p<0.05) Conclusion: Systemic lupus erythematosus, long-term steroids, Mycophenolate Mofetil, Cyclophosphamide and Dyspnea are associated with severe COVID-19.